Identificación de malezas dicotiledóneas prevalentes en cultivos de interés agrícola en el valle de Huánuco - Vidal Jaimes, Edwin (2017)
The weeds, vegetable species that grows spontaneously in cultivated fields and affect the quality and quantity of production, due to competition for water, light and nutrients, they are both plants that have a great potential because, it is considered that they own medicinal properties, therefore, the identification is necessary. The proposed aims in this research work were to determine the prevalence and incidence of dicotyledonous weeds in four agricultural areas of Huanuco. 24 different species of weed were identified, determining like prevalent the following species: Bidens pilosa L., Chenopodium album L. y Sonchus oleraceus L. The cultivated species of sweet potato, beets, corn and alfalfa present a greater variability in species of weed, and have been identified as the most prevalent of the following species: Amaranthus dubius Mart, Bidens pilosa L., Chenopodium album L., Galinsoga parviflora Cav. y Sonchus oleraceus L.